International Companion to John Galt - Kidd, Colin; Carruthers, Gerard (International companions to Scottish literature., 2017)
John Galt (1779-1839) was a contemporary of Sir Walter Scott and Jane Austen, and a friend and biographer of Lord Byron. Although a prolific writer, and much admired in his own lifetime, Galt has never achieved comparable levels of literary fame, and his works -- poised between Enlightenment and Romanticism -- are now often overlooked. Yet his reputation has been slowly growing, and he has attracted critical interest as both a political novelist and a chronicler of Scottish life. This International Companion builds on a steady stream of recent scholarship, and examines Galt's writings in the social, economic, and religious contexts of their time.